Mystery Science Theater 3000 presents. Deathstalker and the warriors from Hell [videorecording (DVD)]. - Hodgson, Joel, 1960-; Nelson, Michael J.; Murphy, Kevin, 1956-; Corbett, Bill, 1960- (Shout Factory, 2015)
Not content to leave well enough alone, Roger Corman extended the 'Deathstalker ' juggernaut with this third installment of the 'Lordish of the Ringish' fantasy about a warrior; an evil wizard; and the jewel that seems to make the difference. Also contains bonus feature.